The Development of Gifted and Talented Well-Being Module (Qalbun Salim) on The Issue of Social Anxiety Among Muslim Gifted and Talented Students in GENIUS Insan College - Amnah Zanariah Abd Razak; Wan Ahmad Zakry Wan Kamaruddin; Ahmad Fuad Mohamad Amin; Diani Mardiana Mat Zin; Amirah Zainun; Nor Hamizah Ab Razak; Daniel Fandi Ngieng; Nor Raihan Zulkefly (Human Resource Management Academic Research Society, 2024)
Indexed by ERA